Penggunaan Media Potongan Kertas Gambar untuk Meningkatkan Pemahaman Materi Animasi Stopmotion - Banne Ima Gasong (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
Creativity in the entertainment industry especially animated film industry that uses stop motion technique is still low. This is evident from the few number of animated films with stop motion techniques that have been produced. This paper aims to improve the understanding of stop motion animation material. The subjects of the study were taken from case study in class XI Multimedia 2 SMKN 1 Dlanggu 2016/2017 academic year number of 30 students. The research method used is descriptive method with qualitative approach. The pattern of research is to improve the understanding of how to create an animated scene using pieces of drawing paper arranged in such a way. By going through the editing process using 2-dimensional animation processing software and applications on android, stop motion camera. From the results of research that is obtained because the process of complexity and requires a high resilience in making animation with the technique, causing the tendency of students just do it so careless that the film images obtained can not be maximized. The conclusion of the research is to use the media of the drawing paper will improve the understanding of stop motion animation material on the students of class XI Multimedia 2 SMKN 1 Dlanggu 2016/2017 academic year number of 30 students.